Male breast cancer: Modified radical mastectomy or breast conservation surgery? A case report and review of the literature. (2017) - Giunta, Gabriele; Rossi, Matteo; Toia, Francesca; Rinaldi, Gaetana; Cordova, Adriana
Abstract: Introduction: Male breast cancer (MBC) is a rare disease that accounts for <1% of breast cancer cases. The most common treatment is modified radical mastectomy (MRM). Recently, breast conservative surgery (BCS) is getting popular for MBC treatment. We report a case and reviewed the literature to investigate whether emerging BCS can be considered as an alternative of a more radical surgery. Presentation of case: A 46 y.o. patient, presented with a painless left breast lump over a period of six months. The patient underwent a quadrantectomy at another institution. Pathology revealed an intraductal carcinoma in close proximity to the margins of excision. Adjuvant hormonal therapy was proposed to the patient, who refused and was referred to our Institution. We performed a MRM and a sentinel lymph node biopsy (SLNB). A contralateral breast liposuction and an adenectomy were also performed. The patient underwent also a nipple-areolar complex reconstruction. The patient didn't receive adjuvant therapy. Discussion: Both oncological safety and satisfactory cosmetic outcomes are the goals of MBC treatment. No specific guidelines for MBC treatment have been proposed. MRM is currently the surgical gold standard of MBC (approximately 70% of all cases). Some authors reported that male BCS associated with radiation therapy is a feasible alternative MRM. Taking into account data from the literature and considering the previous surgery, in the case we report, we offered a MRM, SLNB and a contralateral breast symmetrization. Conclusion: MRM with SLNB and reconstruction of male breast asymmetry should be still considered as the treatment of choice of MBC.